MOTHER’S FEEDING PRACTICE IN PROVIDING NUTRITIOUS FOOD FOR CHILDREN - Sri Hendrawati; Wiwi Mardiah; Rizky Maudina (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2019)
Improper feeding practice in children is one of the causes of nutritional problems in developing countries. This case causes 1.5 million children to die. Feeding practice is a behavior to control the types and the amount of food for children. This study aimed to identify the mother feeding practice to children in the provision of nutrition in a PAUD at Jatinangor sub-district. This study used a descriptive quantitative approach. The population in this study were mothers who had children aged 3-6 years, respondents were chosen using total sampling technique. There were 55 respondents in this study. Data collection used a CFPQ questionnaire (Comprehensive Feeding Practice Questionnaire) to identify the mother's feeding practice. Data were analyzed using the 75 percentile value of the total score of the questionnaire. Data is presented using frequency distribution. The result showed that 39 (70.9%) mothers had poor feeding practice and 16 (29.1%) mother had good feeding practice. These results illustrate that mother feeding practice is still not appropriate in fulfilling nutrition for children. Nurses as a health worker are expected to improve mothers’ knowledge regarding how to apply good and balanced food that appropriate with children's need.Keywords: Children, feeding practice, nutritional status of children.